Crimes of Reason: On Mind, Nature, and the Paranormal by Stephen E. Braude - McDaniel, Stan (Journal of Scientific Exploration, 2014)
Here we have a collection of Stephen E. Braude's challenging philosophical forays into the criticism and evaluation of conceptual frameworks endemic to current trends in science of mind and reality (including the paranormal). Some of the essays in this volume are expanded and updated versions of previously published ones, and some have been written especially for this publication. It is good to welcome the new essays, and good also that the earlier ones should not be lost sight of, as all of them have ongoing value in the ferment surrounding questions of who and what we humans are, what is our relationship to the world, and how much of that relationship can be explained by a science committed to mechanism. Because of the scope and variety of the included essays I will not attempt to discuss each in turn or even to discuss all of them. I will instead give a general sense of what Braude is up to, what is the overall structure of the book, and what a reader may expect to encounter. I will then take just one of the many possible directions a reviewer might take in considering such a multifaceted topic. That particular direction is of considerable interest to me personally and may also, I believe, be of interest to many readers. But there are lots of other directions that might be taken among the variety of topics and ideas to be found in this volume. Each essay is a unique contribution in itself. Taken together they fall roughly into four not entirely unrelated categories. (1) The first two essays deal with the inadequacy of mechanistic explanations in the behavioral and life sciences. The first of these is "Memory Without a Trace," Braude's definitive rejection of the theory that memory consists of data stored in the brain. The second is Braude's review of Rupert Sheldrake's controversial A New Science of Life, where he uses a gentle touch (he considers Sheldrake a personal friend) but eventually must conclude that Sheldrake's theory is "seriously flawed." (2) The third essay, "In Defense of Folk Psychology: Inner Causes versus Action Spaces," takes a penetrating look at the inadequacy of psychological explanation when it tries to attribute human behavior to an "inner cause" (i.e. to brain states). I will be exploring this essay at some length in what follows. (3) The fourth and fifth essays, which are "The Creativity of Dissociation" and "Multiple Personality and Moral Responsibility," add to the author's already extensive analyses in his book First Person Plural (Braude 1995) dealing with issues of multiple personality. (4) The sixth and seventh essays discuss the nature and limits of human abilities as seen from the viewpoint of parapsychological studies. The sixth, "Parapsychology and the Nature of Abilities," is a penetrating look at the failure of clarity in "the scholarly community" regarding "the nature of human (and other organic) abilities." The topic, of course, involves the nature and frequency of occurrence of psi abilities in the populace as a whole. This topic spills over into the seventh essay, "Some Thoughts on Parapsychology and Religion," which I found especially stimulating. I will devote some time below to this essay. There is also an eighth essay, "Credibility under Fire: Advice to the Academically Marginalized," which in my opinion would best be read first. It is a proper introduction to all those which precede it.